Classical Liberalism and its Limits (Philosophy and Progress, 2016)
It is widely considered that minorities rights and dignity are protected in liberal societies particularly in western liberal countries up to a level humanly possible. However, in this article I show that its not as much heroic a theory as we conceive specifically when the liberal society is committed to accommodate plurality of ideas and lifestyles. After briefly explaining principal tenets of classical liberalism I claim that some fundamental weakness of the theory makes it untenable in liberal plural society let alone non-western society of diversityPhilosophy and Progress, Vol#55-56; No#1-2; Jan-Dec 2014